2017
DOI: 10.1186/s12906-017-1919-5
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and personality traits in so-Yang type males

Abstract: BackgroundThe purpose of the present study was to examine the body composition of So-Yang type males according to Sasang constitutional medicine, which is popular in Korea. Different Sasang constitutional types are associated with different muscle distributions, body shapes, and disease susceptibilities. We used the Sasang Personality Questionnaire (SPQ) as a measure of the temperament of each Sasang type.MethodsIn total, 953 subjects aged over 20 years were recruited in Korea. We collected anthropometric para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…There was a positive correlation between the heat pattern and the above anthropometric indices. Yoon J et al observed that the indicators of body water balance (extracellular water/intracellular water ratio and extracellular water/total body water ratio) and Sasang personality questionnaire scores were significantly different between the So-Yang and non-So-Yang types [ 21 ]. Additionally, Jang E et al evaluated whether SCTs could be a risk factor for abdominal obesity in Korean populations.…”
Section: Discussionmentioning
confidence: 99%
“…There was a positive correlation between the heat pattern and the above anthropometric indices. Yoon J et al observed that the indicators of body water balance (extracellular water/intracellular water ratio and extracellular water/total body water ratio) and Sasang personality questionnaire scores were significantly different between the So-Yang and non-So-Yang types [ 21 ]. Additionally, Jang E et al evaluated whether SCTs could be a risk factor for abdominal obesity in Korean populations.…”
Section: Discussionmentioning
confidence: 99%
“…Facial images, body shapes, voice analysis, and questionnaire responses on personality and physiological symptoms were integrated into a multinomial logistic regression analysis. The diagnostic accuracy of SCAT has been reported to be higher than that of QSCC II, which is commonly used for the diagnosis of SCT [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, there have been several reports on the relationship between personality traits and individual characteristics affecting muscle mass. While BMI, an index of body size, has been used as a variable in these studies, some research has specifically examined the relationship between obesity and personality traits 23 , 24 . Although physical activity has positive effects on health, different personality traits tend to have different individual health-related perceptions and behaviors 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…While BMI, an index of body size, has been used as a variable in these studies, some research has specifically examined the relationship between obesity and personality traits 23 , 24 . Although physical activity has positive effects on health, different personality traits tend to have different individual health-related perceptions and behaviors 24 , 25 . Particularly, many studies have investigated on personality traits based on the Big Five theory, one of the most popular international personality classifications, and in a review article, physical activity was positively associated with extraversion and conscientiousness, whereas neuroticism was negatively associated 26 .…”
Section: Introductionmentioning
confidence: 99%